Significance of new Q waves and their location in postoperative ECGs after elective on-pump cardiac surgery: An observational cohort study. Issue 5 (May 2017) - Mauermann, Eckhard; Bolliger, Daniel; Fassl, Jens; Grapow, Martin; Seeberger, Esther E.; Seeberger, Manfred D.; Filipovic, Miodrag; Lurati Buse, Giovanna A.L.
Abstract : BACKGROUND: The clinical significance of new pathological Q waves after on-pump cardiac surgery is uncertain. OBJECTIVES: To determine whether or not either the occurrence per se or the location of new pathological Q waves after on-pump cardiac surgery is associated with 12-month, all-cause mortality and/or major adverse cardiac events (MACEs). DESIGN: Observational cohort study. SETTING: Single university hospital from January 2007 to October 2010. PATIENTS: Consecutive adult patients undergoing elective on-pump cardiac surgery with MACE-free survival until at least the 7th postoperative day and available ECGs both preoperatively and on the 7th postoperative day ( n  = 1464). We conducted a subgroup analysis in patients undergoing isolated coronary artery bypass grafting ( n  = 740). MAIN OUTCOME MEASURE: Our primary endpoint was 12-month, all-cause mortality and/or MACE, defined as acute coronary syndrome, cardiac arrest, congestive heart failure or re-vascularisation at 12 months. Using logistic regression, we examined the prognostic value of new pathological Q waves according to the Minnesota ECG Code, adjusting for the EuroSCORE II, cardiopulmonary bypass time and peak postoperative troponin T concentrations. RESULTS: We included 1464 patients (74% men; mean ± SD age 66 ± 10 years) and observed 103 (7.0%) all-cause deaths and/or MACEs at 12 months. A total of 236 patients (16.1%) had definite or probable new pathological Q waves according to the Minnesota ECG Code. The occurrence of new pathological Q waves per se was not associated with our primary endpoint [adjusted odds ratio, 0.970 (95% confidence interval, 0.540 to 1.648)]. However, the occurrence of a new pathological Q wave in V1 to V5 (anterior) was a strong independent predictor for poor outcome [adjusted odds ratio, 3.461 (95% confidence interval, 1.501 to 7.242)]. CONCLUSION: The current analysis suggests that for patients undergoing elective on-pump cardiac surgery, only new pathological Q waves in V1 to V5 (anterior) in the 7th postoperative day ECG are associated with 12-month, all-cause mortality and/or MACE. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT00468598. Abstract : Supplemental Digital Content is available in the text